Potential Role of Low-Molecular-Weight Dioxolanes as Adjuvants for Glyphosate-Based Herbicides Using Photosystem II as an Early Post-Treatment Determinant - Ewa Szwajczak; Edyta Sierka; Michał Ludynia (Cells, 2023)
Pesticide use cannot be completely abandoned in modern agriculture. Among agrochemicals, glyphosate is one of the most popular and, at the same time, most divisive herbicide. Since the chemicalization of agriculture is detrimental, various attempts are being made to reduce it. Adjuvants—substances that increase the efficiency of foliar application—can be used to reduce the amount of herbicides used. We propose low-molecular-weight dioxolanes as adjuvants for herbicides. These compounds quickly convert to carbon dioxide and water and do not harm plants. The aim of this study was to evaluate the efficacy of RoundUp® 360 Plus supported by three potential adjuvants: 2,2-dimethyl-1,3-dioxolane (DMD), 2,2,4-trimethyl-1,3-dioxolane (TMD), and (2,2-dimethyl-1,3-dioxan-4-yl)methanol (DDM), on a common weed species Chenopodium album L., under greenhouse conditions. Chlorophyll a fluorescence parameters and analysis of the polyphasic fluorescence (OJIP) curve, which examines changes in the photochemical efficiency of photosystem II, were used to measure plant sensitivity to glyphosate stress and verified the efficacy achieved by tested formulations. The effective dose (ED) values obtained showed that the weed tested was sensitive to reduced doses of glyphosate, with 720 mg/L needed to achieve 100% effectiveness. Compared to the glyphosate assisted with DMD, TMD, and DDM, ED was reduced by 40%, 50%, and 40%, respectively. The application of all dioxolanes at a concentration equal to 1 vol.% significantly enhanced the herbicide’s effect. Our study showed that for C. album there was a correlation between the change in OJIP curve kinetics and the applied dose of glyphosate. By analyzing the discrepancies in the curves, it is possible to show the effect of different herbicide formulations with or without dioxolanes at an early stage of its action, thus minimizing the time for testing new substances as adjuvants.